ANALISIS DAN PROFIL TINGKAT KEBUGARAN MAHASISWA JURUSAN TEKNIK MESIN DAN INDUSTRI UNIVERSITAS GADJAH MADA YOGYAKARTA - Herianto dan Chusla Rosdiana Dewi (Universitas Gadjah Mada, 2012)
Aerobic fitness can be used as a health indicator. The purpose of this study is to investigate the effect of Body Mass Index,gender, and physical activity on the aerobic fitness. Twenty females and 27 males students in range of 20 ± 1.2 yearsold, height 164 ± 8.95 cm, and weight 58.23 ± 9.5 kg that meet inclusion criteria were used as subject that measuredin Ergonomics Laboratory Gadjah Mada University within room temperature 25-26oC and 40-50% in humidity.Four methods of indirect measurement (VO2max as an output) is used to measure aerobic fitness: nonexercise skinfoldmeasurements and Body Mass Index, Astrand bicycle, treadmill, and the fitness index Harvard Step Test performed ondifferent days. The results showed that gender (rs = 0.838 on the nonexercise BMI) and BMI (rs = -0.677 on the Astrandmethod) effect on aerobic fitness. The average value of VO2max (ml.kg-1.min in-1) is achieved from each method. Formale, Astrand bicycle = 53.24 ± 7.82, treadmill = 38.43 ± 9, 05, BMI = 44.85 ± 3.45, 42.49 ± 3.38 = skinfold. Forwomen, Astrand bicycle = 47.86 ± 8.59, ± 5.73 treadmill = 34.1, BMI = 34.25 ± 2.46, 34.63 ± 2.51 = skinfold.